Newcastle disease virus vaccine strains: Immunogenicity is not influenced by ICPI - Orsi, M. A.; Doretto Júnior, L.; Reischak, D.; da Silva, L. H. A.; Spilki, F. R.; Buzinaro, M. G. [UNESP]; Arns, C. W. (FapUNIFESP (SciELO), 2009)
Intracerebral pathogenicity index (ICPI) and mean death time (MDT) were determined using commercial live vaccines against Newcastle disease available in Brazil. The ICPI profiles obtained for B1 vaccine strains were nonvirulent and varied from 0 to 0.19, and their MDT was 104-116 hours. The LaSota strains had an ICPI varying between 0.02 and 0.37 and MDT from 92 to 116 hours. ICPI and MDT for the Clone 30 were 0.11 and 104 hours, respectively. For Ulster vaccines, ICPI and MDT were 0 and >150 hours; for VG-GA was 0.03 and 140 hours; and for C2, 0.04 and >144 hours. Eye drop vaccination and IM challenge, at the 1 st week and the 4 th week, respectively, resulted in highest protection for B1 (95-100%) and LaSota (90-100%) strains. The variability in vaccine ICPI did not interfere with immune response and all vaccines provided similar protection. All vaccines were considered non virulent and were classified as lentogenic according to the immunobiological product standards.
Keywords: Intracerebral pathogenicity index (ICPI); Mean death time (MDT); Newcastle disease virus (NDV) vaccines; Aves; Newcastle disease virus